2019
DOI: 10.3389/fmed.2019.00300
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage Depletion Mitigates Platelet Aggregate Formation in Splenic Marginal Zone and Alleviates LPS-Associated Thrombocytopenia in Rats

Abstract: Sepsis is often accompanied with thrombocytopenia partly due to platelet sequestration in the lung and liver. The spleen can store up to one-third of circulating platelets and can also significantly affect platelet transfusion outcomes by accumulating platelets. However, in sepsis, it is not clear whether there are platelet changes in the spleen which could contribute to sepsis-associated thrombocytopenia and also influence platelet transfusion outcomes. By using confocal microscopy, we examined endogenous rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 41 publications
(42 reference statements)
1
5
0
Order By: Relevance
“…Our studies demonstrate that anti-α IIb β 3 antibody-induced platelet sequestration in the spleen resembles that observed in Rasa3-mutant mice. Furthermore, a similar pattern of splenic MZ platelet accumulation was described for a rat model of sepsis-induced thrombocytopenia (51), i.e., in a situation where a weak platelet agonist (lipopolysaccharide) induces platelet clearance. Thus, altered integrin function may also contribute to splenic platelet clearance in acquired thrombocytopenias.…”
Section: Discussionsupporting
confidence: 59%
“…Our studies demonstrate that anti-α IIb β 3 antibody-induced platelet sequestration in the spleen resembles that observed in Rasa3-mutant mice. Furthermore, a similar pattern of splenic MZ platelet accumulation was described for a rat model of sepsis-induced thrombocytopenia (51), i.e., in a situation where a weak platelet agonist (lipopolysaccharide) induces platelet clearance. Thus, altered integrin function may also contribute to splenic platelet clearance in acquired thrombocytopenias.…”
Section: Discussionsupporting
confidence: 59%
“…Platelets and macrophages can mutually regulate each other’s functions at least during inflammation [ 25 , 26 , 27 , 28 , 29 , 30 ]. The great number of mediators released by these effector cells forms a complex chain of events.…”
Section: Discussionmentioning
confidence: 99%
“…41 It is not surprising that the expression of pro-inflammatory cytokines and the infiltration of neutrophils and macrophages in the spleen was significantly increased after LPS stimulation. 42 These increased neutrophils and macrophages not only are recruited to the injured heart to participate in the inflammatory response and promote the apoptosis of cardiomyocytes, but also further exacerbate systemic inflammation, which results in a vicious cycle that induces multiple organ dysfunction. Previous study showed that RvD1 activates spleen remodeling after myocardial infarction, thereby improving ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…As the largest immune organ, the spleen plays an important role during LPS‐induced systemic inflammation 41 . It is not surprising that the expression of pro‐inflammatory cytokines and the infiltration of neutrophils and macrophages in the spleen was significantly increased after LPS stimulation 42 . These increased neutrophils and macrophages not only are recruited to the injured heart to participate in the inflammatory response and promote the apoptosis of cardiomyocytes, but also further exacerbate systemic inflammation, which results in a vicious cycle that induces multiple organ dysfunction.…”
Section: Discussionmentioning
confidence: 99%